2007
DOI: 10.1016/j.yexmp.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

M-30 and 4HNE are sequestered in different aggresomesin the same hepatocytes

Abstract: M-30 and 4HNE adducts are two markers of active liver disease. M-30 is a serologic marker and 4HNE adducts are histologic markers. M-30 is a marker for apoptosis because it is a fragment of cytokeratin-18 left over from proteolysis by caspase 3. 4HNE is a marker of oxidative stress because it results from lipid peroxidation. Both markers are commonly found in nonalcoholic steatohepatitis and in alcoholic hepatitis. Liver biopsies from patients with steatohepatitis, 11 alcoholic and 11 nonalcoholics were staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Immunodetection of M30 has been used to demonstrate hepatocyte apoptosis in situations histologically analogous to alcoholic hepatitis, such as nonalcoholic steatohepatitis [25]. The M30 neoepitope can be detected in Mallory-Denk bodies and liver cell aggresomes in both alcoholic and nonalcoholic steatohepatitis [26]. In connection with this, M30 immunoreactivity in our study was predominantly found in the vicinity of neutrophilic inflammatory infiltrates.…”
Section: Discussionsupporting
confidence: 73%
“…Immunodetection of M30 has been used to demonstrate hepatocyte apoptosis in situations histologically analogous to alcoholic hepatitis, such as nonalcoholic steatohepatitis [25]. The M30 neoepitope can be detected in Mallory-Denk bodies and liver cell aggresomes in both alcoholic and nonalcoholic steatohepatitis [26]. In connection with this, M30 immunoreactivity in our study was predominantly found in the vicinity of neutrophilic inflammatory infiltrates.…”
Section: Discussionsupporting
confidence: 73%
“…Staining for 4-HNE was remarkably increased in all the groups of OLETF rats treated with ethanol. The OLETF rat livers also showed 4-HNE adduct aggresomes within hepatocytes, which was more prominent in rat livers treated with ethanol for 5 d/wk (arrow) (33). There was moderate staining for 4-HNE in the livers of OLET rats treated with ethanol for 5 d/wk ( Figure 6A).…”
Section: Staining Of 4-hne In Oletf and Olet Rat Livers After Treatmementioning
confidence: 91%
“…At this stage, the proteins are not longer degradable by the proteasome. This results in the formation of protein aggregates, hydrophobic and insoluble in nature, referred to as “aggresomes” (Amidi et al, 2007). The formation of aggresomes can be thermodynamically driven by their exposed hydrophobic residues and the by-products of lipid peroxidation (like MDA or HNE) can cause covalent cross linking (Jung et al, 2009) The proteasomal activity decreases in aging cells and it has been shown that proteasomal inhibition in young cells leads to the enhanced formation of (polyubiquinated) protein aggregates (Powell et al, 2005).…”
Section: Theories Of Aging and How They Shape The Definitions Of Smentioning
confidence: 99%